Analisis Kemampuan Berpikir Kreatif Siswa dalam Menyelesaikan Soal Ditinjau Dari Self-Esteem Matematis Pada Materi Bilangan Bulat Kelas VII SMP - Anastasia Sari; Jamilah Jamilah; Dewi Risalah (LPD Universitas PGRI Pontianak, 2026)
This study aims to describe students' mathematical creative thinking abilities in solving mathematics problems in terms of mathematical self-esteem on integer material for VII grade of junior high school. The research method used was qualitative with a case study approach. The research subjects were 26 students of VII grade at SMP Pancasila. Data collection techniques included creative thinking ability tests, mathematical self-esteem questionnaires, and interviews. The results showed that most students had mathematical self-esteem in the moderate category, and their creative thinking ability was also dominated by the moderate category. The creative thinking ability of students with high, moderate, and low self-esteem showed different variations, where there is not always a linear relationship between mathematical self-esteem and creative thinking ability. This indicates that other factors influence students' creative thinking abilities in solving mathematical problems. The conclusion of this study is that students' creative thinking abilities in solving integer problems vary at each level of mathematical self-esteem, necessitating attention to both cognitive and affective aspects in mathematics learning.